Mother, Fetal and Disease History Factors as a Preeklampsia Risk in Asia and Africa: A Meta-Analysis - Edoardo Calini (International Journal of Science and Society, 2020)
Background: Preeclampsia accounts for nearly 10 percent of maternal deaths in Asia and Africa. Therefore, it is important to detect signs and symptoms early on by knowing the factors that are at risk for a mother experiencing preeclampsia. Objective: To determine the risk factors for preeclampsia in Asia and Africa through the application of meta-analysis. Method: A systematic review was carried out on 26 case-control and cohort studies related to risk factors for preeclampsia from four databases (PubMed, BioMed Central, ProQuest, and Google Scholar). The pooled odds ratio was calculated with the fixed-effect and random-effect model using Review Manager 5.3. Result: A total of 20 studies consisting of 2,954,769 women were included in the meta-analysis. Risk factors for preeclampsia based on maternal factors were chronic hypertension=9.74(95% CI 1.69-56.04), gestational diabetes=9.28(95% CI 4, 49-19.19), pre-pregnancy body mass index=2.70(95% CI 2.08-3.50), maternal age during pregnancy=2.37(95% CI 2.29-2.46) and nulliparity=2.08(95% CI 1.44-3.01). The fetal factor was multiple pregnancy=4.24(95% CI 3.14-5.73). Four disease history factors were family history of preeclampsia=13.99(95% CI 6.91-28.33), history of chronic hypertension=8.28(95% CI 5.92- 11.59), history of preeclampsia=OR 6.90(95% CI 3.58-13.31) and family history of hypertension=2.81(95% CI 1.75-4.50). Conclusion: The results of a meta-analysis of 10 risk factors for preeclampsia could be used as a screening tool to determine the magnitude of risk and early diagnosis of preeclampsia that allows timely intervention.